2011
DOI: 10.1007/s12159-011-0046-9
|View full text |Cite
|
Sign up to set email alerts
|

A multi-agent and auction-based framework and approach for carrier collaboration

Abstract: Carrier collaboration in transportation means multiple carriers form an alliance to optimize their transportation operations through sharing transportation requests and vehicle capacities. In this paper, we propose a multi-agent and auction-based framework and approach for carrier collaboration in less than truckload transportation. In this framework, the carriers outsource/acquire requests through multiple auctions, one for outsourcing each request; a carrier acts as an auctioneer when it wants to outsource a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…They demonstrated that for information sharing, a decentralized method is superior for maintaining the confidentiality; however, a centralized method surely produces more profitable results. Dai and Chen (2011) proposed order sharing on two decisions-based problem. The first decision is to choose requests that a carrier does not wish to serve and the second decision is to choose requests that are desirable to serve.…”
Section: Order Sharingmentioning
confidence: 99%
“…They demonstrated that for information sharing, a decentralized method is superior for maintaining the confidentiality; however, a centralized method surely produces more profitable results. Dai and Chen (2011) proposed order sharing on two decisions-based problem. The first decision is to choose requests that a carrier does not wish to serve and the second decision is to choose requests that are desirable to serve.…”
Section: Order Sharingmentioning
confidence: 99%
“…When all business organizations create a grand coalition, it is the most concerning alliance formation problem when the collaboration is super-additive. It is addressed in [28], [29], [23], [22], [15], [11]. The super-additivity means that whatever two separate coalitions creating union get at least as much as they get independently.…”
Section: B Model Of Studymentioning
confidence: 99%
“…Closely related work can be found in Berger and Bierwirth (2010), Dai and Chen (2011) where horizontal collaboration between carriers is considered and where each of the carrier agents may act as an auctioneer to outsource transportation requests while the another carrier agents act as bidders. Dai and Chen (2011) explicitly formulates this as a two decision problem, one for the auctioneer and one for the bidder.…”
Section: Literaturementioning
confidence: 99%
“…Dai and Chen (2011) explicitly formulates this as a two decision problem, one for the auctioneer and one for the bidder. By using simulation, they evaluate collaborative approach with (i) the individual planning approach (no job exchange) and (ii) a centralized planning approach.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation